Autoimmunity to Tropomyosin-Specific Peptides Induced by Mycobacterium leprae in Leprosy Patients: Identification of Mimicking Proteins - Singh, Itu; Yadav, Asha Ram; Mohanty, Keshar Kunja; Katoch, Kiran; Sharma, Prashant; Pathak, Vinay Kumar; Bisht, Deepa; Gupta, Umesh D.; Sengupta, Utpal (Frontiers in Immunology, 2018)
Background It has been shown earlier that there is a rise in the levels of autoantibodies and T cell response to cytoskeletal proteins in leprosy. Our group recently demonstrated a rise in both T and B cell responses to keratin and myelin basic protein in all types of leprosy patients and their associations in type 1 reaction (T1R) group of leprosy. Objectives In this study, we investigated the association of levels of autoantibodies and lymphoproliferation against myosin in leprosy patients across the spectrum and tried to find out the mimicking proteins or epitopes between host protein and protein/s of Mycobacterium leprae. Methodology One hundred and sixty-nine leprosy patients and 55 healthy controls (HC) were enrolled in the present study. Levels of anti-myosin antibodies and T-cell responses against myosin were measured by ELISA and lymphoproliferation assay, respectively. Using 2-D gel electrophoresis, western blot and MALDI-TOF/TOF antibody-reactive spots were identified. Three-dimensional structure of mimicking proteins was modeled by online server. B cell epitopes of the proteins were predicted by BCPREDS server 1.0 followed by identification of mimicking epitopes. Mice of inbred BALB/c strain were hyperimmunized with M. leprae soluble antigen (MLSA) and splenocytes and lymph node cells of these animals were adoptively transferred to naïve mice. Results Highest level of anti-myosin antibodies was noted in sera of T1R leprosy patients. We observed significantly higher levels of lymphoproliferative response (p < 0.05) with myosin in all types of leprosy patients compared to HC. Further, hyperimmunization of inbred BALB/c strain of female mice and rabbit with MLSA revealed that both hyperimmunized rabbit and mice evoked heightened levels of antibodies against myosin and this autoimmune response could be adoptively transferred from hyperimmunized to naïve mice. Tropomyosin was found to be mimicking with ATP-dependent Clp protease ATP-binding subunit of M. leprae. We found four mimicking epitopes between these sequences. Conclusion These data suggest that these mimicking proteins tropomyosin and ATP-dependent Clp protease ATP-binding subunit of M. leprae or more precisely mimicking epitopes (four B cell epitopes) might be responsible for extensive tissue damage during type1 reaction in leprosy.